The state policy of Kazakhstan in the space industry: from the implementation of development programs to the formation of the institutional memory of the industry - Medeuov , Zhomart (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2022)
The article deals with the state policy of Kazakhstan in the field of space activities. The author identifies three elements that traditionally underpin public policy in Kazakhstan. The first element is the state’s participation in the industry, which can be in an active or passive phase, depending on the existence of a valid state development program. The second element is the legal framework that regulates relations between all current and potential industry participants. The third element is institutional development, the presence of production infrastructure, organizations, and human capital employed in the industry and emerging activities, established practices, and procedures. The author uses a conceptual approach that assumes that the state, among all possible actors in the space industry and plays a decisive role in it, including due to such a factor as techno-politics, that is, the use of technological and scientific achievements of space in national construction. For this reason, the article is mainly focused on the analysis of state development programs implemented in the space industry over the years of independence. The evolution of the goals and objectives of public policy, its correlation with external risks and opportunities, the results achieved, and the remaining problems are traced. The current global trends in the development of the industry, which challenge the space industry in Kazakhstan, are noted. It is concluded that now, the space industry of Kazakhstan has not achieved its strategic goals – to reach the level of commercial projects with a steady demand for the services provided.